The vision of divine light in Saint Gregory Palamas's theology - F. T. Tomoioagă (Acta Theologica)
The Hesychast debates of the 14th century between the representatives of the Western and Eastern tradition over the issue of the light seen in the experience of prayer are still relevant nowadays. Gregory Palamas – who was the central figure of these debates – was rediscovered in the 20th century by Orthodox Theology and is still in the process of reception in Western theology. The present study represents a synthesis of Saint Gregory Palamas’s teaching on the vision of Divine Light as it was articulated in the debate with his adversaries. Directly linked to this topic are other adjacent issues, namely the Transfiguration of Christ, the intellectual and the mystical knowledge, the nature of the divine energies, the purpose of the Christian life, and so on. The entire study in couched in the frame of a personal reflection over the type of spirituality fit for contemporary man – a contemplative one of a mystical type or a much more practical one, based on social virtues?